Assessment of Changes in the Quality of Life of Emerging Economies in the Context of Developed Economies of the European Union - Pukelienė, Violeta; Starkauskienė, Viktorija (Organizations and Markets in Emerging Economies, 2015)
The present article has focused on the theoretical and practical aspects of the measurement of quality of life by the quality of life index (IQOL). A special focus of the present article is placed on complexity of quality of life measurement. In the article, an integrated Quality of Life Measurement Model and IQOL are formulated on the basis of theoretical assumptions and synthesis of factors of external and internal environments of quality of life and indicators reflecting them. The Quality of Life Measurement Model presented in the article has been empirically tested assessing quality of life in 20 purposefully selected developed and emerging economies of the European Union during the period from 2005 till 2013. The newly created IQOL is one of the ambitions to promote the methodological background for business and political actors and improvement of the quality of life in emerging economies.